The long-run effects of health aid in low-income countries - Keneni G. Negeri (AOSIS, 2023)
Background: Whether health aid has a positive, negative, or no effect on the health status of recipient countries is controversial. Objective:  The current paper examines the long-run effect of health aid on health status in low-income countries. Methods: The long-run health function was estimated using infant mortality as a proxy for health status and panel data constructed from 34 low-income countries from 2000 to 2017. For the estimation, fixed effect, random effect, and Hausman-Taylor estimators were employed. Results: The estimation results indicate that health aid has a beneficial and statistically significant long-run effect on the health status of low-income countries. Doubling health aid saves the lives of 44 infants per 1000 live births in the long run. Conclusion: This study shows that health aid could be one of the best interim tools with which the health status of low-income groups could get improved and helps meet the target of universal health coverage. Despite the favorable effect of health aid observed in this study, recipient countries need to find ways of promoting surrogate domestic health financing systems, as external assistance cannot be an everlasting means of improving population health.